Oligosaccharide and Substrate Binding in the Starch Debranching Enzyme Barley Limit Dextrinase. Issue 6 (27th March 2015) - Møller, Marie S.; Windahl, Michael S.; Sim, Lyann; Bøjstrup, Marie; Abou Hachem, Maher; Hindsgaul, Ole; Palcic, Monica; Svensson, Birte; Henriksen, Anette
Abstract: Complete hydrolytic degradation of starch requires hydrolysis of both the α-1, 4- and α-1, 6-glucosidic bonds in amylopectin. Limit dextrinase (LD) is the only endogenous barley enzyme capable of hydrolyzing the α-1, 6-glucosidic bond during seed germination, and impaired LD activity inevitably reduces the maltose and glucose yields from starch degradation. Crystal structures of barley LD and active-site mutants with natural substrates, products and substrate analogues were sought to better understand the facets of LD–substrate interactions that confine high activity of LD to branched maltooligosaccharides. For the first time, an intact α-1, 6-glucosidically linked substrate spanning the active site of a LD or pullulanase has been trapped and characterized by crystallography. The crystal structure reveals both the branch and main-chain binding sites and is used to suggest a mechanism for nucleophilicity enhancement in the active site. The substrate, product and analogue complexes were further used to outline substrate binding subsites and substrate binding restraints and to suggest a mechanism for avoidance of dual α-1, 6- and α-1, 4-hydrolytic activity likely to be a biological necessity during starch synthesis. Graphical abstract: Highlights: LD activity is essential for complete starch hydrolysis. Active-site LD–substrate complexes spanning the α-1, 6-glucosidic bond were trapped. LD–substrate specificity is delineated by crystallographic subsite localization. α-1, 6-Hydrolytic versus α-1, 4-hydrolytic activity is rationalized. This study shows the facilitation of mutational screening of LD for optimal starch hydrolysis.